Investigating Health Disparities Associated With Multisystem Inflammatory Syndrome in Children After SARS-CoV-2 Infection. Issue 11 (7th September 2022) - Zambrano, Laura D.; Ly, Kathleen N.; Link-Gelles, Ruth; Newhams, Margaret M.; Akande, Manzilat; Wu, Michael J.; Feldstein, Leora R.; Tarquinio, Keiko M.; Sahni, Leila C.; Riggs, Becky J.; Singh, Aalok R.; Fitzgerald, Julie C.; et al.
Abstract : Background: Multisystem inflammatory syndrome in children (MIS-C) is a postinfectious severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2)–related complication that has disproportionately affected racial/ethnic minority children. We conducted a pilot study to investigate risk factors for MIS-C aiming to understand MIS-C disparities. Methods: This case-control study included MIS-C cases and SARS-CoV-2-positive outpatient controls less than 18 years old frequency-matched 4:1 to cases by age group and site. Patients hospitalized with MIS-C were admitted between March 16 and October 2, 2020, across 17 pediatric hospitals. We evaluated race, ethnicity, social vulnerability index (SVI), insurance status, weight-for-age and underlying medical conditions as risk factors using mixed effects multivariable logistic regression. Results: We compared 241 MIS-C cases with 817 outpatient SARS-CoV-2-positive at-risk controls. Cases and controls had similar sex, age and U.S. census region distribution. MIS-C patients were more frequently previously healthy, non-Hispanic Black, residing in higher SVI areas, and in the 95th percentile or higher for weight-for-age. In the multivariable analysis, the likelihood of MIS-C was higher among non-Hispanic Black children [adjusted odds ratio (aOR): 2.07; 95% CI: 1.23–3.48]. Additionally, SVI in the 2nd and 3rd tertiles (aOR: 1.88; 95% CI: 1.18–2.97 and aOR: 2.03; 95% CI: 1.19–3.47, respectively) were independent factors along with being previously healthy (aOR: 1.64; 95% CI: 1.18–2.28). Conclusions: In this study, non-Hispanic Black children were more likely to develop MIS-C after adjustment for sociodemographic factors, underlying medical conditions, and weight-for-age. Investigation of the potential contribution of immunologic, environmental, and other factors is warranted.